2018
DOI: 10.1177/1532673x18788050
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and the Nationalization of State Legislative Elections

Abstract: The electoral fortunes of state parties are partly shaped by the positions adopted by national parties. This creates the potential dilemma: The position that is best for the national party might be too extreme for the electorate in some states. Some state parties attempt to address this problem by adopting more moderate positions than their national-level counterparts. We argue that the efficacy of state party moderation hinges on the degree of polarization at the national level. We develop theory and examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Political science research supports many of these elements. American politics has indeed nationalized and polarized (Campbell 2018b; Caughey, Dunham, and Warshaw 2018; Hopkins 2018; Jacobson 2019; Rogers 2016; Sievert and McKee 2018; Zingher and Richman 2018). The congressional incumbency advantage has receded in recent years, making members increasingly vulnerable to national election tides (Jacobson 2015a).…”
mentioning
confidence: 99%
“…Political science research supports many of these elements. American politics has indeed nationalized and polarized (Campbell 2018b; Caughey, Dunham, and Warshaw 2018; Hopkins 2018; Jacobson 2019; Rogers 2016; Sievert and McKee 2018; Zingher and Richman 2018). The congressional incumbency advantage has receded in recent years, making members increasingly vulnerable to national election tides (Jacobson 2015a).…”
mentioning
confidence: 99%
“…This leads to the conclusion that, “with both elites and voters responding to national instead of state legislative politics, state legislators’ electoral fates appear largely out of their own control” (Rogers 2016, 209). Additionally, the ability of state parties to influence state legislative elections through adopting relatively moderate issue stances is attenuated by high levels of national polarization (Zingher and Richman 2019). Finally, nationalization of state legislative elections reached new heights in the 2018 midterm election, even in the absence of a presidential election (Melusky and Richman 2020).…”
Section: Partisan Polarization Nationalization and State Legislaturesmentioning
confidence: 99%
“…(While nationalization is clearly a more important factor in voting at the federal versus state and local level, we do not wish to overstate the case. See Rogers [2016] and Zingher & Richman [2019].) Indeed, Darr et al (2018) found evidence of less ticket-splitting in areas with local paper closures, suggesting that local papers themselves play an important role in countering the trend toward nationalization.…”
Section: Complicating the News-turnout Connectionmentioning
confidence: 99%